2021
DOI: 10.1108/ijbpa-08-2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of the impact of building envelope systems on embodied and operational carbon of residential buildings

Abstract: PurposeBuildings are responsible for the consumption of around 40% of energy in the world and account for one-third of greenhouses gas emissions. In Saudi Arabia, residential buildings consume half of total energy among other building sectors. This study aims to explore the impact of sixteen envelope variables on the operational and embodied carbon of a typical Saudi house with over 20 years of operation.Design/methodology/approachA simulation approach has been adopted to examine the effects of envelope variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Although the GWP is important, it is not included in the building energy directives of Turkey or other countries. 37 Although the annual greenhouse gas amount per usage area produced from the final energy consumption is specified in the energy performance certificates, the GWP is omitted. This approach has its drawbacks.…”
Section: Resultsmentioning
confidence: 99%
“…Although the GWP is important, it is not included in the building energy directives of Turkey or other countries. 37 Although the annual greenhouse gas amount per usage area produced from the final energy consumption is specified in the energy performance certificates, the GWP is omitted. This approach has its drawbacks.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that openness and reputation are crucial factors affecting users' behavioral use, which in turn, affect their learning performance. Furthermore, Liaw (2008), Li et al (2014), and (Hamida et al, 2022) emphasize the importance of understanding students' perceived satisfaction, behavioral use, and the effectiveness of elearning systems. Liaw (2008) investigates students' satisfaction and behavioral use in the context of the Blackboard system, finding that perceived satisfaction is a significant predictor of behavioral use, which in turn affects learning performance.…”
Section: Behavior To Use Blockchain Ai and E-learning Engagementmentioning
confidence: 99%
“…A parametric study for building an envelope system's impact on operational and embodied carbon of residential building is also introduced by Hamida et al The results of this study indicate that operational carbon represents about 90% of the overall life cycle carbon, whilst embodied carbon accounted for 10%. The sensitivity analysis revealed that the window to wall ratio significantly contributes to an increase in operational carbon by 47.4% [22]. According to a study by Schlueter and Thesseling, requiring building designers to prioritize eco-friendly parameters resulted in more robust design ideas that both fulfil the needs of clients and results in sustainable architecture [23].…”
Section: -Backgroundmentioning
confidence: 99%